PERAN AKUNTANSI LINGKUNGAN DALAM MENINGKATKAN KINERJA LINGKUNGAN DAN KINERJA KEUANGAN PERUSAHAAN - ANIELA, YOSHI (: 2303-1719)
The issue of environmental damage, causes, and the effects on human life either for today’s life or future. This encourage the people to realize the importance of environmental reservation. The company, as the part of the community, is also pursued to participate in environmental reservation. This participation, of course, needs expenses, therefore it is necessary to recognize, disclosure, and presentation of them in an accounting, because the company should responsible all operational and managerial activities to all stakeholders and shareholders. Hence, the merge of green accounting or environmental accounting is a necessity. Environmental accounting is the identification, measurement, and allocation of environmental costs¸the integration of these environmental costs into business decisions, and the subsequent communication of the information to a company’s stakeholders. According the the discussion in this article and supported by the literary study, also empirical and academical studies, it can be revealed that green accounting has the significant and positive impact on the financial and environmental performance. The positive impact of the green accounting on financial is encoraged by the positive perception of consumers to the company in which will encourage the sales vlume and then increase the company profit. The environmental performance, either environmental health or environment vitality is encouraged by the voluntary of the company in copliance to the goverment laws, regulations, and policies and the consumers’ pursue to get the product with environmental oriented